Autophagy in striated muscle diseases - Li, Haiwen; Zhang, Lingqiang; Zhang, Lei; Han, Renzhi (Frontiers in Cardiovascular Medicine, 2022)
Impaired biomolecules and cellular organelles are gradually built up during the development and aging of organisms, and this deteriorating process is expedited under stress conditions. As a major lysosome-mediated catabolic process, autophagy has evolved to eradicate these damaged cellular components and recycle nutrients to restore cellular homeostasis and fitness. The autophagic activities are altered under various disease conditions such as ischemia-reperfusion cardiac injury, sarcopenia and genetic myopathies, which impact multiple cellular processes related to cellular growth and survival in cardiac and skeletal muscles. Thus, autophagy has been the focus for therapeutic development to treat these muscle diseases. To develop the specific and effective interventions targeting autophagy, it is essential to understand the molecular mechanisms by which autophagy is altered in heart and skeletal muscle disorders. Herein, we summarize how autophagy alterations are linked to cardiac and skeletal muscle defects and how these alterations occur. We further discuss potential pharmacological and genetic interventions to regulate autophagy activities and their applications in cardiac and skeletal muscle diseases.